Faculty Members’ Perceptions Towards Online Learning at Mid-West University During of Covid-19 Pandemic - Shahi, Sushil Kumar (Journal of Entrepreneurship & Management Studies, 2024)
This study was conducted to analyze Mid-West University faculty members' perceptions towards online learning activities initiated by the university during COVID-19 Pandemic. The objective of this research was to explain faculty perceptions, experiences, and challenges while creating an online learning environment in the Mid-West University, Nepal. The phenomenological research design was used with the focus on a qualitative research approach. Using a purposive sampling, 10 faculty members were considered for a written interview as the respondents. Analysis of the data collected through the interviews reveals both the encouraging and the painful experiences on the side of the faculty members when conducting the online classes. The finding of the study is that MU was able to create a success story of online teaching-learning activities during the COVID-19 Pandemic with the due responsibility to work hard in the future for promotion of an online teaching-learning platform.